2004
DOI: 10.1016/s0921-4488(03)00255-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of diarrhoea caused by rotavirus and Escherichia coli in lambs in Kashmir valley, India

Abstract: One hundred and twenty-nine faecal samples, collected over a period of 1 year, from 96 diarrhoeic and 33 non-diarrhoeic lambs aged between 0 and 3 months were examined for presence of rotavirus and Escherichia coli (E. coli). Group A rotavirus was detected in 24 (25%) of diarrhoeic lambs using sandwich enzyme linked immunosorbent assay (ELISA) and ribonucleic acid-polyacrylamide gel electrophoresis (RNA-PAGE). Statistically no significant relation was found between rotavirus infection and age of the lambs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
10
1
1
Order By: Relevance
“…Clonal spread of a common strain was not detected among the animals tested in the present study. in small ruminants from Turkey (Gokce et al 2010) and other states (Wani et al 2004), however, research on classification of enterovirulent E. coli and its virulence genes is limited. Recent studies have reported (Wani et al 2003;Bhat et al 2008;Bandyopadhyay et al 2011), the existence of at least one virulence gene in 41%, 36.7%, and 32.6% of E. coli isolates, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Clonal spread of a common strain was not detected among the animals tested in the present study. in small ruminants from Turkey (Gokce et al 2010) and other states (Wani et al 2004), however, research on classification of enterovirulent E. coli and its virulence genes is limited. Recent studies have reported (Wani et al 2003;Bhat et al 2008;Bandyopadhyay et al 2011), the existence of at least one virulence gene in 41%, 36.7%, and 32.6% of E. coli isolates, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, E. coli was isolated from 58% diarrhoeic lambs in India (Wani et al 2004b). Of the 234 isolates, only 74 strains (32%) carry at least one virulence gene characteristic for STEC.…”
Section: Discussionmentioning
confidence: 99%
“…Although RV causes diarrhea in different species like human infants, calves, lambs, goat kids, piglets and puppies in different parts of the world (Georges et al 1984, Garcia et al 2000, Wani et al 2004Dhama et al 2009), reports regarding circulation of AvRVs are scarce in India. Wani et al (2003) first detected the mammalianlike electropherogroup AvRVs from chicken with diarrhea.…”
Section: Epidemiologymentioning
confidence: 99%